URGENSI PEMBUATAN PERATURAN DESA TENTANG SISKAMLING DI DESA KOTO MESJID - Jayakusuma, Zulfikar; Aprilia, Aisyah Dwi; Andanil, Najwa Putri (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2025)
This community service initiative investigates the pressing need to implement a Village Regulation concerning the Neighborhood Security System (SISKAMLING) in Koto Mesjid Village, addressing emerging security challenges such as reduced community engagement, heightened environmental risks, and the lak of uniform security protocols. The primary aim is to bolster community awareness and ensure organized governance for maintaining public safety at the village level.The approach employed integrades field observations, stakeholder interviews, community workshops, and participatory discussions to collaboratively identify current challenges and establish regulatory requirements. The findings reveal that the community is in strong favor of creating a formal SISKAMLING regulation, acknowledging that well-defined guidelines, roles, and operational standards are crucial for enhancing coordination, accountability, and the sustainability of security efforts. This initiative improves the village’s preparedness in preventing disturbances, promotes shared responsibility, and strengthens local resilience trhough a legal framework that meets community needs.